2017
DOI: 10.1016/j.jdiacomp.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Towards an improved global understanding of treatment and outcomes in people with type 2 diabetes: Rationale and methods of the DISCOVER observational study program

Abstract: The DISCOVER program will provide insights into the current management of patients with type 2 diabetes worldwide, which will contribute to informing future clinical guidelines and improving patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 36 publications
0
93
0
Order By: Relevance
“…Key strengths of the DISCOVER study programme include the large numbers of patients and inclusion of many lower‐middle and upper‐middle‐income countries which have rarely or never been studied before . The use of a standardized electronic case report form for data collection allows comparison of results within and across countries and regions.…”
Section: Discussionmentioning
confidence: 99%
“…Key strengths of the DISCOVER study programme include the large numbers of patients and inclusion of many lower‐middle and upper‐middle‐income countries which have rarely or never been studied before . The use of a standardized electronic case report form for data collection allows comparison of results within and across countries and regions.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for the DISCOVER study programme have been reported in detail elsewhere, and are briefly summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…The scope of DISCOVER is ambitious and holistic, with the goal of obtaining as detailed a picture as possible of the management of T2D across the globe, and to highlight specific areas for improvement in the included countries that might also be applicable to other countries. Data on physiological variables (including height, weight and seated blood pressure), laboratory test results (including glycated haemoglobin [HbA1c] and fasting plasma glucose measurements), glucose‐lowering treatments (including reasons for treatment selection), socio‐economic and demographic characteristics, and clinical and patient‐reported outcomes are collected by clinicians during routine visits . A mixed methodology is used for data collection: investigators use an electronic (or paper) case report form to record patient clinical data at study visits and information from patient medical records is automatically extracted in countries where this is possible (Canada, Denmark, France, Norway and Sweden).…”
Section: The Global Discover Studymentioning
confidence: 99%
“…The DISCOVER study programme (http://clinicaltrials.gov identifiers: NCT02322762 and NCT02226822 [J‐DISCOVER, in Japan]) was set up to address the knowledge gaps in the management and clinical outcomes of people with T2D. The overarching aim of the programme is to describe patient characteristics, evolution of disease management patterns and clinical outcomes over 3 years in people with T2D who are initiating a second‐line glucose‐lowering therapy in a real‐world setting.…”
Section: The Global Discover Studymentioning
confidence: 99%
See 1 more Smart Citation